DEFISIENSI VITAMIN D TERHADAP PENYAKIT (Vitamin D Deficiency and Diseases) - Pusparini Pusparini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
It has been estimated that deficiency and insufficiency of Vitamin D affect one bilion people worldwide. Vitamin D deficiency can befound not only in countries with four (4) seasons, but also in countries with sunlight exposure all year long The objective of this studywas to know whether vitamin D deficiency can occur in Indonesia as well and to explore the role of vitamin D in people‘s health, althoughIndonesia is a country in the equator region. To avoid long term negative health consequences 25 hydroxyvitamin D/25 (OH) D serumlevel should be between 30 and 100 ng/mL. The main source of vitamin D is by synthesis at the skin which is exposed to ultraviolet Bradiation. The other source of vitamin D is from food. There are a lot of causes of vitamin D deficiency, for example: decreased vitaminD synthesis, nutritional intake of vitamin D, maternal vitamin D stores and exclusive breastfeeding, mal absorption and decreasedsynthesis or increased degradation of 25 (OH) D. From the above factors, decreased vitamin D synthesis is the main cause of vitamin Ddeficiency. The vitamin D deficiency is estimated and plays an important role in multiple disorders, such as: osteoporosis, fracture, cancer,cardiovascular disease, diabetes mellitus, autoimmune disease and infectious disease. A good strategy in managing vitamin D deficiencyis needed in order to solve the related problems.